Growth and production of the copepod community in the southern area of the humboldt current system - Escribano, R., Bustos-Ríos, E., Hidalgo, P. and Morales, C.E. (My University, 2015)
Zooplankton production is a critical issue for understanding marine ecosystem structure and dynamics, however, its time-space variations are mostly unknown in most systems. In this study, estimates of copepod growth and production (CP) in the coastal upwelling and coastal transition zones off central-southern Chile (&sim35&ndash37° S) were obtained from annual cycles during a 3 year time series (2004, 2005, and 2006) at a fixed shelf station and from spring&ndashsummer surveys during the same years. C-specific growth rates (g) varied extensively among species and under variable environmental conditions however, g values were not correlated to either near surface temperature or copepod size. Copepod biomass (CB) and CP were higher within the coastal upwelling zone (<50 km) and both decreased substantially from 2004 to 2006. Annual CP ranged between 24 and 52 g C m&minus2 year&minus1 with a~mean annual P/B ratio of 2.7. We estimated that CP could consume up to 60% of the annual primary production (PP) in the upwelling zone but most of the time is around 8%. Interannual changes in CB and CP values were associated with changes in the copepod community structure, the dominance of large-sized forms replaced by small-sized species from 2004 to 2006. This change was accompanied by more persistent and time extended upwelling during the same seasonal period. Extended upwelling may have caused large losses of CB from the upwelling zone due to an increase in offshore advection of coastal plankton. On a larger scale, these results suggest that climate-related impacts of increasing wind-driven upwelling in coastal upwelling systems may generate a negative trend in zooplankton biomass.
Keywords: copepod community, Zooplankton, Humboldt Current